2016
DOI: 10.1016/j.scs.2016.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pavement materials on surface temperatures in tropical environment

Abstract: Loss of natural habitat and increased use of man-made materials have led to higher temperatures in tropical urban landscape. One way to handle this issue is by using paving materials that absorb less amount of heat and provide lower surface temperatures. This paper identifies several pavement materials with low surface temperatures for potential use in a tropical climate. The study was conducted in Putrajaya, Malaysia. Paving materials selected were Blue Impala polished granite (BIPG), Rosa Tanggo polished gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…Materials with high reflection rates cause a reduction in the environmental temperature and the various surfaces' temperature via convection [56]. Benrazavi et al [57] investigated the effect of various material types commonly used for floors on the surface temperature in equatorial climates. Some information regarding the materials causing higher reductions in the ambient temperature was provided therein.…”
Section: Albedomentioning
confidence: 99%
“…Materials with high reflection rates cause a reduction in the environmental temperature and the various surfaces' temperature via convection [56]. Benrazavi et al [57] investigated the effect of various material types commonly used for floors on the surface temperature in equatorial climates. Some information regarding the materials causing higher reductions in the ambient temperature was provided therein.…”
Section: Albedomentioning
confidence: 99%
“…The increasing urbanization of the subtropics is producing expanding urban areas with high density and a growing number of tall buildings [1]. The reduction of natural scenery and the proliferation of human-made buildings and pavement are increasing the temperatures of urban environments [2] and the heat storage capacity of buildings and the ground [3], thereby magnifying the urban heat island effect. This effect is a unique phenomenon in terms of temperature distribution and distinguishes urban environments from rural ones in terms of temperature research [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…From a large-scale survey involving 1050 respondents, Wong et al identified that majority of the respondents reported respiratory problems (90.2%) followed by heat exhaustion (83.1%) and heat cramps (72.9%) as the health externalities of urban heat in KLMC [17]. Beside a substantial impact on the deterioration of urban quality and liveability, very little studies are dedicated on the UHI mitigation measures in the local context [18,19].…”
Section: Introductionmentioning
confidence: 99%